Interpersonal Bundling - Chen, Yongmin; Zhang, Tianle (Management Science, 2015)
This paper studies a model of interpersonal bundling, in which a monopolist offers a good for sale under a regular price and a group purchase discount if the number of consumers in a group—the bundle size—belongs to some menu of intervals. We find that this is often a profitable selling strategy in response to demand uncertainty, and it can achieve the highest profit among all possible selling mechanisms. We explain how the profitability of interpersonal bundling with a minimum or maximum group size may depend on the nature of uncertainty and on parameters of the market environment, and we discuss strategic issues related to the optimal design and implementation of these bundling schemes. Our analysis sheds light on popular marketing practices such as group purchase discounts, and it offers insights on potential new marketing innovation. This paper was accepted by J. Miguel Villas-Boas, marketing.